Cystatin-C as a Marker of Cognitive Function in Elders: Findings from the Health ABC Study - Yaffe, Kristine (2008)
We determined if serum cystatin-C, a novel measure of kidney function that also co-localizes with brain β-amyloid, is associated with cognitive function among 3030 Black and White elders (mean age, 74 years). Elders with high cystatin-C (N=445, 15%) had worse baseline cognitive scores on 3MS (p=0.01) or DSST (p=0.02) compared to those with intermediate (N=1008, 33%) or low level (N=1577, 52%) and more pronounced decline over 7 years (p=0.002 and p=0.04). Multivariate adjustment led to similar results. Incident cognitive impairment (decline of ≥1.0 SD) was greatest among those with high cystatin-C (3MS: 38% vs. 25%, adjusted OR=1.92; 95%CI 1.37-2.69; DSST: 38% vs 26%, OR= 1.54; 95% CI 1.10-2.15).